Depiction of global trends in publications on mobile health - Foozonkhah, Shahla; Kalankesh, Leila R. (International journal of one health, 2017)
Background: Variety of mobile health initiatives in different levels have been undertaken across many countries. Trends of these initiatives can be reflected in the research published in m-health domain. Aim: This paper aims to depict global trends in the published works on m-health topic. Materials and Methods: The Web of Science database was used to identify all relevant published papers on mobile health domain worldwide. The search was conducted on documents published from January 1898 to December 2014. The criteria for searching were set to be “mHealth” or “Mobile health” or “m health” or “m_health” or “m-health” in topics. Results: Findings revealed an increasing trend of citations and publications on m-health research since 2012. English was the first most predominant language of the publication. The US had the highest number of publication with 649 papers; however, the Netherlands ranked first after considering publication number in terms of countries population. “Studies in Health Technology and Informatics” was the source title with highest number of publications on mobile health topics. Conclusion: Trend of research observed in this study indicates the continuing growth is happening in mobile health domain. This may imply that the new model of health-care delivery is emerging. Further research is needed to specify directions of mobile health research. It is necessary to identify and prioritize the research gaps in this domain.